Heat lightning - Sandford, John, 1944 Feb. 23-; Logan, Chuck, 1942- (New York : Berkley Books, 2009)
Summoned by Lucas Davenport to investigate a pair of murders in which the victims are found with lemons in their mouths, Minnesota Bureau of Criminal Apprehension investigator Virgil Flowers struggles to find a connection that could prevent additional killings.
Includes an excerpt of the author's "Rough Country," (p. [415]-432)
"Written in cooperation with ... Chuck Logan" -- Acknowledgments.
Keywords: Vietnam War, 1961-1975 -- Veterans -- Crimes against -- Fiction; Government investigators -- Minnesota -- Fiction; Minnesota -- Fiction; Mystery fiction